Pengaruh Pengaruh Model Pembelajaran Multiliterasi Berbantuan Photo Story terhadap Kemampuan Menulis Narasi Siswa Sekolah Dasar: Pengaruh Model Pembelajaran Multiliterasi Berbantuan Photo Story terhadap Kemampuan Menulis Narasi Siswa Sekolah Dasar - Urifah, I'in Dewi; Fradana, Ahmad Nurefendi Fradana (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The research was carried out because it was found that the narrative writing ability of class IV at SD Negeri Lebo was still low in Indonesian language subjects. This research was conducted with the aim of improving the ability to write narratives at Lebo State Elementary School using a multiliteracy model assisted by photo stories. This research uses quantitative experimental methods using the One Group Pretest Posttest type (One Group Pretest Posttest Design). The population of this research was 20 class IV students using research instruments in the form of student ability tests before treatment (pretest) and after implementing learning or treatment (posttest). The data collection techniques are tests, observation and documentation with data analysis techniques using statistical data. The research results showed that the average value of the posttest data reached 76.10, which was greater than the pretest average which reached 56.35 with the results of the average value of the pretest value and posttest value having significant differences. So it can be concluded that the application of the multiliteracy model assisted by photo stories has an effect on the ability to write narratives for class IV at Lebo State Elementary School.